Partisipasi Masyarakat Dalam Pengembangan Wisata Watu Gambir Di Desa Karang Kecamatan Karangpandan Kabupaten Karanganyar - Fitriyati, Rohmah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
Abstract This research aims to analyze community participation in developing Watu Gambir Tourism. The population in this research is the people of Karang Village, Karangpandan District, consisting of BUMDes groups, business actors and local community leaders. The design used in this research is descriptive research with a document recording data collection method which is then analyzed using qualitative descriptive analysis. The research results show that community participation is good, tourism development not only contributes to economic aspects, but also to the social welfare of the community. Keywords: Decision Making, Evaluation, Development.